Is investment in Africa too low or too high? : macro and micro evidence - Devarajan, Shantayanan, 1954- 1954- (Policy research working paper, 2001)
Many analysts decry the level of investment in Africa, saying it is too low. But there is no evidence, in cross-country data or in microeconomic data from Tanzania, that private and public capital is productive in Africa. In that sense, investment in Africa may be viewed as too high